2004
DOI: 10.1177/0095399703258684
|View full text |Cite
|
Sign up to set email alerts
|

Increased Injury Risk among First-Day Skiers, Snowboarders, and Skiboarders

Abstract: First-day participants should be targeted in any future educational programs with emphasis on gear selection, use of protective gear, and the risks of exceeding the limits of their ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 33 publications
2
45
0
2
Order By: Relevance
“…In addition, advanced snowboarders had significantly fewer injuries compared with beginners 19. Also, other studies showed higher injury rates for beginner skiers and snowboarders compared with experts 20 21. However, types of activities or high-speed manoeuvres perfor med by exper t sk iers and snowboarders may i ncrease t he r isk of sustaining a more severe injury compared with beginners 22…”
Section: Discussionmentioning
confidence: 95%
“…In addition, advanced snowboarders had significantly fewer injuries compared with beginners 19. Also, other studies showed higher injury rates for beginner skiers and snowboarders compared with experts 20 21. However, types of activities or high-speed manoeuvres perfor med by exper t sk iers and snowboarders may i ncrease t he r isk of sustaining a more severe injury compared with beginners 22…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have documented that the frequency and severity of snowboarding injuries are linked to the degree of experience and speed 1 2 10 15. However, our impression from past years and from the results of a pilot study is that many snowboarders suffer injuries at slow or moderate speeds, and that the probability of snowboard injuries may be linked to a concatenation of several risk factors (unpublished data from internal survey).…”
Section: Introductionmentioning
confidence: 99%
“…Second, although our hospital is located less then 6 km from SnowWorld, patients could have been brought to other hospital. Furthermore, several risk factors, i.e., experience level [19], alcohol consumption [20], place of accident on the slope, e.g., fun parks (recreation areas containing terrain to perform tricks) [18,21] and skill level [22] were not taken into account.…”
Section: Discussionmentioning
confidence: 99%